(untitled) (Journal Of Educational and Psychological Researches, 2023)
The present study aims to identify the effectiveness of deductive group patterns in developing the creative thinking of second-intermediate-grade pupils in history discipline. The current null hypothesis has been investigated: There are no statistically significant differences at (0.05) between the scores mean of the experimental group pupils who were taught according to the deductive group pattern and the scores mean of the control group pupils who were taught according to traditional method in creative thinking testing. the study sample was divided into two groups: an experimental group of (30) female students and a control group of (31) female students. The two groups are equalized based on the variables of age, the scores of the first course in Islamic history, intelligence, pre-test of creative thinking, and parent educational level. The researcher identifies the teaching content as the fourth and fifth sections selected from the Arabic Islamic history text of the second intermediate grade for the academic year (2015-2016). According to the content, the researcher put (83) behavioral objectives: (44) for the fourth chapter and (39) for the fifth chapter. The researcher adopted the Torrance creative thinking test which was modified by alseid Keerallh (1981). The tool is modified by the researcher to suit the content and ensure its validity and reliability